Calculate the Longitude and Orbital Motion for Amaletha, Europa, Ganymede and Callisto Satellites - Ibrahim, Rasha (Iraqi Journal of Science, 2023)
The orbital motion and longitude for some Jupiter's satellites (Amaletha, Europa, Ganymede and Callisto) were calculated from two different locations Iraq and Syria. A program was designed, the input parameters were the desired year, month, day and the longitude of the location, the output parameters results were applied in form of a file, and this file includes the longitude, orbital motion, and local time of these satellites. A specific date 1-10-2013 was taken, the results of longitude was (20-336) º and orbital motion was (92-331) º for both Iraq and Syria location with observing time (05:24:14-15:18:10) for Iraq and (04:56:33-14:50:30) for Syria. The difference in time between the two locations was constant (00:45:00), these results were compared with the results of Gilbert in 1974, but he worked only on the longitude with respect to the universal time, which his values was (34-296)º.